Prevalence of nasal congestion amid hospital labor - Ferreira Gomez, B. (2010)
Nasal congestion is a very common symptom that often accompanies the processes of infectious virus and allergic rhinitis; interfering with the quality of life and work of the patient may lead to a significant shrinkage of psychosocial interaction. Despite the scarce epidemiological data from the investigational point of view, the present study sought to assess the prevalence of nasal congestion in a population of workers from three hospital sites, Centro Hospitalar de Coimbra, E.P.E., Hospital Sobral Cid and the IDT, I.P. Delegação Regional do Centro.Methodology: The study was conducted during the months of March, April and May 2008. A questionnaire was used for identification of seven symptoms occurring in the last two weeks and the symptoms occurred in the last week. The index of nasal congestion was calculated through the transformation of the first seven questions of the questionnaire. The descriptive statistics, ANOVA and factorial analysis of correspondence were used; the level of statistical significance was p <0.05.Results and conclusions: 912 workers answered the questionnaires applied. For the seven questions that define the index of nasal congestion, we obtained a reliability coefficient of 0,873 and a suitability of KMO 0,892. Having made the transformation a reclassification of the index of nasal congestion in four classes resulted in the following: 20.6% of respondents showed no symptoms (class A), 58,5% showed mild symptoms (class B), 19% showed mild to moderate congestion (class C) and 2.2% reported severe symptoms (Class D). The fact that 21.2% of respondents refer severe or moderate symptoms is suggestive that the prevalence of nasal congestion in the study population is significant. It emphasizes the need for early diagnosis and treatment of this symptom so common in clinical practice.